Magnetohydrodynamic Effects on Double Diffusion of Non‐Newtonian Hybrid Nanofluid in Circular Eccentric Annuli - Israt Jahan Supti; Md. Mamun Molla; Preetom Nag; Sadia Siddiqa; Souhail Souai (Engineering Reports)
ABSTRACT The numerical investigation conducted in this study focuses on the heat and mass transfer in magnetohydrodynamic non‐Newtonian power‐law fluid flow of temperature‐dependent Al2O3–Fe3O4–water hybrid nanofluid within cylindrical annuli across four different eccentricities. This type of problem finds widespread application in various engineering contexts, where hybrid non‐Newtonian fluids offer enhanced efficiency for cooling and insulation purposes. In this configuration, the inner circle of the geometry is hot while the outer circle is cold, with the nanofluid filling the space between the cylinders. The governing equations are simulated using the Galerkin weighted residual finite element method. Various parameters are controlled in the study, including the Rayleigh number ranging from 104 to 106, power‐law index ranging from 0.7 to 1.4, nanoparticle volume fraction ranging from 0% to 4%, Hartmann number ranging from 0 to 30, Buoyancy ratio ranging from −1 to 1, and Lewis number ranging from 1 to 10, in addition to the fixed Prandtl number (6.8377). The study presents visualizations such as streamlines, isotherms, and iso‐concentration contours, along with the assessment of heat and mass transfer rates expressed in terms of Nusselt and Sherwood numbers. The findings reveal that the heat transfer rate increases with higher nanoparticle volume fraction, Rayleigh number, and Buoyancy ratio. Similarly, the mass transfer rate is enhanced with increased Rayleigh number, Lewis number, and power‐law index. Notably, elevating the power‐law index leads to a decrease of 50.1% in the local Nusselt number and 52.4% in the local Sherwood number, respectively. With n=0.7 and ϕ=0, increasing Ra from 104 to 106 raises Nu‾ and Sh‾.